Methods for kinematic analysis of human movement in military applications: A review of current and prospective methods - Volf, Petr; Kutílek, Patrik; Hejda, Jan; Vítečková, Slávka; Smrčka, Pavel; Hána, Karel; Svoboda, Zdeněk; Křivánek, Václav (Lékař a technika, 2019)
Expansion of methods employed in the kinematic analysis of human movement for diagnosing of the physical and mental health of subjects can be traced back to the 1990`s when new information technologies and electronic recording systems started their development boom. Evaluation methods of body movement for the diagnostics of physical and mental health expanded significantly in clinical practice. This study presents an overview of these methods with the focus on how applicable the analysis of human movement can be in military practice, where they are currently marginally used. The aim of this study is to offer some recommendations on how particular methods could be utilized in an army context. This article also suggests the most appropriate methods of quantitative evaluation for posture and motion control in the course of standing, gait and other activities carried out in military training and active duty.
Keywords: Gait Analysis; ozbrojené síly; lidé; Posture; biomechanika; postura těla; Humans; analýza chůze; Military Personnel; Kinesiology, Applied; Biomechanical Phenomena; kineziologie aplikovaná